ANALYSIS OF SUSTAINABILITY OF ECONOMIC SECTOR IN PROBOLINGGO DISTRICT EAST JAVA PROVINCE – INDONESIA - Markus Patiung; Nugrahini Susantinah Wisnujati (Socio-Economics/Agribusiness Department, 2020)
Gross Regional Domestic Product (PDRB) is the amount of gross added value arising from all economic sectors in the region. It aims to help formulate regional policies, plan and evaluate development results, and provide information that can describe the regional economic performance. The purpose of this research is to analyse sustainable economic sector in Probolinggo district east Java province – Indonesia. A sustainable sector means a sector that is currently included as a basis and will remain a basis sector in the future even if the growth is slow or fast. The analytical methods used include analysis of Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Klassen Typology. Of the 17 economic sectors that contributed to the PDRB of Probolinggo district, with the results of the LQ analysis, 7 sectors were in basic categories and 10 sectors were in non-basic categories. Results of the comparative analysis of LQ and DLQ indicates that there are 5 leading sectors, 2 prospective sectors, 6 mainstay sectors, and 4 lagging sectors. The results of the classification typology analysis consisted of 3 fast-growing and fast-growing sectors, 7 sectors is growing fast, 4 advanced and slow-growing sectors, and 3 relatively lagging sectors. From the three analysis results, it can be seen that the sustainable sectors are agriculture, forestry, and fisheries (second rank ); electricity and gas procurement sector (first rank); water supply, waste management, waste and recycling sectors (third rank); health service sector and social activities (fourth rank); other service sectors (rank fifth); processing industry sector; construction sector; transportation and warehousing sector; the accommodation and food and drink provision sector; information and communication sector; and the education services sector.